Research of influence of the metal nature on the mechanism of polyvinylpyrrolidone metal copolymers synthesis - Suberlyak, Oleh; Grytsenko, Oleksandr; Hischak, Krystyna; Hnatchuk, Natalia (Publishing House of Lviv Polytechnic National University, 2013)
The influence of the metal fine filler nature on the polymerization mechanism of polyvinylpyrrolidonemethacrylate compositions in the presence and without iron(II) sulphate has been determined. The catalysis mechanism has been confirmed via complexation with charge transfer between the initial composition components. The metal activating effect increases with the increase of its negative electrochemical potential. Встановлено вплив природи металевого диcперсного наповнювача на закономірності полімеризації полівініл- піролідон-метакрилатних композицій в присутності і без домішок сульфату заліза (ІІ). Підтверджено механізм каталізу через комплексоутворення з перенесенням заряду між компонентами вихідної композиції. Встановлена зростаюча активуюча дія металу із зростанням його від‘ємного електрохімічного потенціалу.
Дослідження впливу природи металу на закономірності синтезу металонаповнених кополімерів полівінілпіролідону
Keywords: polyvinylpyrrolidone; kinetics; complexation; catalysis; metal-hydrogels; полівінілпіролідон; кінетика; комплексоутворення; каталіз; металогідрогелі